Urgency of Teaching English to Young Learners in Kurikulum Merdeka Belajar - Ni Putu Artila Dewi*; Made Dita Sintadewi; Made Detri Suryantini (Universitas Syiah Kuala, 2021)
The research aims to analyze perceptions about the importance of English for Young Learners at Elementary Schools at Gugus Diponogoro in Jembrana Regency in ‘Kurikulum Merdeka Belajar’. The research objective was to find out teachers’ perceptions about the importance of English for young learners at Elementary Schools in Jembrana Regency. The sample of the research was 16 teachers from 12 Elementary Schools in Gugus Diponogoro. The samples were taken through cluster random sampling. The researcher used descriptive qualitatif and the data were collected by using questionnaire. The results of the research were 1) The students are able to master English when teaching English since earlier, 2) English will be useful in gaining a job in the future, and 3) By mastering English, the young learners will have the social and economic benefits in the future. Therefore, it can be concluded that the teachers of Elementary Schools in Gugus Diponogoro agreed that English for Young Learners is crucial to teach.